Development of shoot primordia in tissue culture of Papaver somniferum L. - M. Ovecka; Bobák, M.; Samaj, J.
The first step during shoot primordia development in Papaver somniferum L. was the differentiation of globular meristemoids, resulting from localized cell division in callus tissue. During meristemoid maturation differences observed were in mitotic activity, cytoplasmic density, starch distribution, and in cell size, cell shape, and nucleus size to cell size ratio between peripheral and central meristemoid cells. Cell specialization within the meristemoids is a prerequisite for shoot primordia development.